Movimentos de intervenção no marco regulatório das organizações da sociedade civil no Brasil [manuscrito]: trabalho e lógicas institucionais - Carlos Eduardo Guerra Silva (2014)
The regulatory framework of civil society organizations (CSOs) ensures the legal formalization of initiatives oriented not-for-profit, and deals with the certification and funding of public interest organizations. Currently, several laws and processes which comprise the regulatory framework present limitations for the development of Brazilian CSOs. Based on organizational institutionalism perspectives, this study analyzes how the logics and work of intervention movements are configured into the regulatory framework of civil society organizations in Brazil. The intervention movements are comprised of organizational actors aligned around emergent logics intending to transform current norms. Institutional logics represent systems of beliefs and meanings thereby providing conceptions for action that are connected to practices articulated by the institutional work of the movements. In 2010, the Third Sector Law Movement held the logic that the Philanthropy Law (Law n. 12,101/2009) is unconstitutional and jeopardizes the operations of organizations certified as charities. The Platform for a New Regulatory Framework for Civil Society Organizations, constituted by numerous nationally functioning CSOs, was another initiative that emerged in 2010. The Platform grounds its logics on the necessity of a State policy that fosters public interest organizations without bureaucracy, providing legal certainty and holding control mechanisms that ensure transparency without compromising autonomy of action. Based on a multiple case study, the courses of the movements were observed from 2010 to 2013. The Third Sector Movement undertook activities aimed primarily as legal interventions: a) establishment of a collective writ of mandamus for the charity members of the federation who have led the movement; b) articulation of an unconstitutional action process, with includes charities in national ambit. The Platform developed activities aimed mainly at: a) establishment of its governance system; e b) concretion of working group with Federal Government and the proposal of the regulatory framework. The logics of both movements incorporate representation principles of public and corporative interests through which the political and technical forms of institutional work are developed. The political work seeks to legitimate the movements through the fields mobilization, mediation of logics as well as generating social and material support. The technical work, which involves experts and working groups, justifies logics and creates conceptual rigor on ideas for legitimating the movements. Based on these interactive configurations of institutional work, the movements mediated logics and consubstantiated social practices that circulated mainly through the Executive and Judiciary powers of the State, which also involved the participation of other civil society groups. Although regulatory adjustments have occurred during the analyzed period, desired claims have not yet been achieved, evidencing that regulatory change can be time consuming, and may only occur in a piecemeal way or even not materialize as expected. Regardless of incompletions, a (re)configuration of the CSOs representation networks have emerged with extensive coverage, technical and political capabilities, contiguous logics and currently working as a result of an institutionalization process of which its effect for the strengthening of the civil society can potentially be more relevant than the immediate matter of consolidating the one regulatory framework